Effectiveness of Problem Based Learning Device Development to Improve Generic Science Skills - Via Monica Devi; Susilawati Susilawati; I Wayan Gunada (Journal of Science and Science Education, 2021)
This development research aims to develop an effective problem-based physics learning device model to improve students' generic science skills. The type of research used is Research and Development (R&D) using a 4D model. This 4D model consists of four stages, namely Define, Design, Develop and Disseminate. The effectiveness of the learning device was obtained based on the analysis of the observation sheet on the implementation of the lesson plans from three observers was then determined using the calculation of the Interjudge Agreement (IJA) and the N-Gain test. Based on the results of the research that has been carried out, the results of the IJA calculation analysis show that the implementation of learning is above 75% with the N-Gain test results of 0.54 are in the medium category, while the average value for the pretest value is 36.91 and the average posttest value 68.75. So it can be said that the problem based model of physics learning tools used is effective in improving the generic science skills of students